The features of chronic neuropathic pain syndrome forming at traumatic injury of nerves of extremities - V. I. Tsymbaliuk; S. N. Nelepin; A. N. Nikiforova; N. A. Sapon (Ukrainian Neurosurgical Journal, 2010)
On the material of 110 supervisions of patients with traumatic injury of nerves of extremities influence of different factors on chronic neuropathic pain syndrome (CNPS) forming was studied. On the base of statistic analysis it was sat that PS origin statistically for certain depends on patient’s sex and age, and on time passed from trauma to appeal foe neurosurgical help. There were considerably more women than men among injured patients (75 and 35.7% accordingly). At patients younger than 46 years peripheral nerves’ trauma was accompanied by PS development in 33.3% cases, from 45 to 59 years — in 66.6%, older than 60 years — almost in 100%. With increasing of time passed from trauma to operation, the amount of patients with PS also considerably increased.The reliable dependence of CNPS development from trauma’s type (isolated or combined), it’s character (open or closed), injured nerve topography (upper or lower extremity) and type of preliminary treatment was not exposed.